Proceedings of the First International Conference Economic and Business Management 2016 2016
DOI: 10.2991/febm-16.2016.28
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Liquidity Risk of Deposit and Loan Maturity Mismatch in Commercial Banks

Abstract: Commercial banks must maintain a certain degree of mismatch to improve the efficiency of the use of money, but excessive maturity mismatch may cause liquidity risk. Based on that, this paper introduced the latest rules of the Basel Ⅲ, analysis the term structure of assets and liabilities and the liquidity situation. We create a model of liquidity gap to give evaluation of the liquidity risk, referring to the requirements of the net stable funding ratio. According to the result of liquidity risk measurement, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The banking industry, academia and supervisors place a relatively greater emphasis on capital requirements than on liquidity and funding, reflecting the general view that a solvent bank will be liquid (Shi and Liu, 2016). However, the global financial crisis of 2009-2011 confirmed that a lack of liquidity might become one of the first causes of crisis phenomena, and lead to bank insolvency and bankruptcy.…”
Section: The Maturity Structure Of Bank Assets and Liabilities: A Thementioning
confidence: 99%
“…The banking industry, academia and supervisors place a relatively greater emphasis on capital requirements than on liquidity and funding, reflecting the general view that a solvent bank will be liquid (Shi and Liu, 2016). However, the global financial crisis of 2009-2011 confirmed that a lack of liquidity might become one of the first causes of crisis phenomena, and lead to bank insolvency and bankruptcy.…”
Section: The Maturity Structure Of Bank Assets and Liabilities: A Thementioning
confidence: 99%